Del Gaudio S. On the nature of surzyk: a double perspective - Бріцин, В.; Саплін, Ю.; Труб, В. (Мовознавство, 2011)
Рецензія на книгу: Del Gaudio S. On the nature of surzyk: a double perspective (Wiener slawistischer almanach, sonderband 75) München ; Berlin ; Wien, 2010.— 328 p.